Starość – ostoją wiary w świetle akt męczeńskich (Sylwetki męczenników – starców) - Gacia, Tadeusz (Vox Patrum, 2011)
From twenty two martyrs of advanced age described in ancient Christian texts the author has choosen four in order to present his thesis that old age is a support for faith. They are: Polycarp of Smyrna, Potinus – a bishop of Lyons, presbyter Saturninus from among the martyrs of Abitene, and Sixtus – the bishop of Rome. The literary prototype of Christian martyr – senex is Eleazar whose martyrdom is described in the second and fourth books of the Maccabees. He was an old man, who at the time his cruel death preserves the courage of spirit and becomes a support and example of faith for the young.